2019
DOI: 10.1108/sbm-11-2018-0095
|View full text |Cite
|
Sign up to set email alerts
|

Sport content and virtual reality technology acceptance

Abstract: PurposeNotwithstanding the dynamics of digital transformation and its relevance for revenue generation in the entertainment industry, empirical research that focused on consumer behavior at the intersection of sport content and media technology acceptance is limited. Virtual reality (VR) is a re-emerging and nowadays commercially available technology that impacts sport consumed through media. The purpose of this paper is to investigate the consumer acceptance of VR technology and highlight the effects of conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 94 publications
1
32
0
Order By: Relevance
“…2, 3, 4). This result is also consistent with previous studies that confirmed the significant influence of PE on sport VR context acceptance (Kunz and Santomier 2019) and on E-mail acceptance (Mao and Palvia 2008). Hsu and Lin (2008) reported that PE plays critical factor in work-related environment and given that the respondents considered in this study were chemical operators and employees, this suggests that regardless of the group, respondents perceive that using IVR technology in chemical industry training would increase their job performance.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 2 more Smart Citations
“…2, 3, 4). This result is also consistent with previous studies that confirmed the significant influence of PE on sport VR context acceptance (Kunz and Santomier 2019) and on E-mail acceptance (Mao and Palvia 2008). Hsu and Lin (2008) reported that PE plays critical factor in work-related environment and given that the respondents considered in this study were chemical operators and employees, this suggests that regardless of the group, respondents perceive that using IVR technology in chemical industry training would increase their job performance.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…On the other hand, Kunz and Santomier (2019) used the extended UTAUT 2 model to investigate the acceptance of VR technology in sport content reported that only 3 out of 7 factors (i.e. PE, SI, and HM) showed significant effects on behavioural intention to adopt IVR system (Kunz and Santomier 2019). As observed, the IVR adoption intention results from both studies are different.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies have been used flow theory for understanding user behaviour in using technology (Kaur et al, 2016a; Kunz & Santomier, 2019; Lin et al, 2020; Naglis & Bhatiasevi, 2019). However, Choi et al (2007, p. 227) noted the flow research situation in the field of IS as ‘too broad and ill‐defined due to the numerous ways it has been operationalized, tested, and applied’.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the disruptive potential of digitalization for sport management practice, sport management research has scarcely addressed these topics. However, some researchers have investigated the application of virtual and augmented reality in sport marketing (Goebert and Greenhalgh, 2020; Kunz and Santomier, 2019; Uhm et al , 2020), the acceptance of wearables (Kim and Chiu, 2019; Kim et al , 2019) and usage intentions of smart devices (Song et al , 2018). Furthermore, the mobile consumption of news coverage has developed new opportunities regarding the on-demand consumption of live sport via Internet broadcasting (Hutchins, 2019; Keating, 2018; Lindholm, 2019).…”
Section: Literature Review: Digital Transformation In Sport Management Researchmentioning
confidence: 99%